2019
DOI: 10.5194/acp-19-3557-2019
|View full text |Cite
|
Sign up to set email alerts
|

Saharan dust and biomass burning aerosols during ex-hurricane Ophelia: observations from the new UK lidar and sun-photometer network

Abstract: Abstract. On 15–16 October 2017, ex-hurricane Ophelia passed to the west of the British Isles, bringing dust from the Sahara and smoke from Portuguese forest fires that was observable to the naked eye and reported in the UK's national press. We report here detailed observations of this event using the UK operational lidar and sun-photometer network, established for the early detection of aviation hazards, including volcanic ash. We also use ECMWF ERA5 wind field data and MODIS imagery to examine the aerosol tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 80 publications
(120 reference statements)
4
58
0
1
Order By: Relevance
“…According to previous studies (Borge et al, 2007;Guo et al, 2017;Osborne et al, 2019;Zheng et al, 2015), backward trajectories for identified particulate matter pollution episodes were computed using Numerical Atmospheric-dispersion Modelling Environment to identify the impacts of transboundary air pollution and local PM pollution in Hong Kong (Jones et al, 2007). Briefly, the Numerical Atmospheric-dispersion Modelling Environment model is a Lagrangian transport model that is driven by model forecast winds or reanalysis data with variable spatial resolutions (Walters et al, 2017).…”
Section: 1029/2019jd031140mentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies (Borge et al, 2007;Guo et al, 2017;Osborne et al, 2019;Zheng et al, 2015), backward trajectories for identified particulate matter pollution episodes were computed using Numerical Atmospheric-dispersion Modelling Environment to identify the impacts of transboundary air pollution and local PM pollution in Hong Kong (Jones et al, 2007). Briefly, the Numerical Atmospheric-dispersion Modelling Environment model is a Lagrangian transport model that is driven by model forecast winds or reanalysis data with variable spatial resolutions (Walters et al, 2017).…”
Section: 1029/2019jd031140mentioning
confidence: 99%
“…Ground-based light detection and ranging (lidar) is a useful instrument for monitoring the vertical structure of atmosphere at high temporal and spatial resolution, especially in the PBL (e.g., Fan et al, 2019 ;Liu et al, 2013 ;Manninen et al, 2018 ;Osborne et al, 2019 ;Pearson et al, 2010 ;Qin et al, 2016 ;Su et al, 2018). In particular, ground-based Doppler lidars can be deployed to remotely monitor vertical and horizontal winds and mixing processes to identify aerosol transport in the lower level of the atmosphere and to explore dynamic features of the PBL (Barlow et al, 2011;Harvey et al, 2013;Manninen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies such as [14] show that transport over larger ranges are expected during April through June, while vertical transport is highest from April through September. Under certain meteorological conditions, significant amounts of Saharan dust are transported north, over the Mediterranean basin [15][16][17] and in severe cases, even over Western, Central, and Eastern Europe [18][19][20][21]. Dust outbreaks have been observed as far as northern Europe and the Baltic Sea [10,22].…”
Section: Introductionmentioning
confidence: 99%
“…On the morning of October 16 th 2017 a red sky phenomenon was reported on several sites of the United Kingdom (UK) (Telegraph, 2017), as a result of the high aerosol loadings in the overlying atmosphere (Harrison et al, 2018;Osborne et al, 2019), while similar reports on the morning of October 17 th were given for the Netherlands as well (NLTIMES, 2017). These high aerosol loadings were the result of transport of desert dust from Northern Africa and smoke from Iberian wildfires.…”
mentioning
confidence: 83%